CHALLENGES IN THE RECEPTION WITH RISK CLASSIFICATION FROM THE PERSPECTIVE OF NURSES - Raiane Antunes Sampaio; Adelmo Martins Rodrigues; Fernanda Costa Nunes; Alessandra Vitorino Naghettini (Universidade Federal do Paraná, 2022)
Objective: to understand the challenges perceived by nurses in the process of reception with risk classification. Method: this is a qualitative, analytical research, conducted with nurses working in the reception with risk classification in four Emergency Care Units in the North-Central region of Goiás, Brazil, in the period from October 2019 to February 2020. Results: the following thematic categories emerged, characterized as difficulties faced in the emergency service in view of the perception of the nurse classifier: "Demand issues"; "Informational issues"; "Care issues" and "Organizational issues". Conclusion: we found demand challenges that contribute to overcrowding as an outcome, and informational, care, and organizational challenges understood as basic challenges. This study helps the intervention in a timely manner to modify the reality of the health service.